1991
DOI: 10.1002/nbm.1940040206
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and quantitation in proton spectroscopy

Abstract: Localized proton NMR spectroscopy in the human brain is one of the more technically advanced applications of human in vivo NMR spectroscopy. Spin/echo techniques introduced reliable localization procedures, whereas the introduction of phase encoding techniques improved the spatial information content considerably. Using the sensitivity of the 1H NMR signal, a spatial resolution of 7 X 7 X 15 mm can be obtained. Chemical shift images can be reconstructed to represent the choline, creatine, N-acetyl aspartate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Water-suppressed, localized proton spectra were obtained using a Philips Gyroscan 1.5 T combined imaging and spectroscopy system (2). Multislice images were obtained in three planes.…”
Section: Methodsmentioning
confidence: 99%
“…Water-suppressed, localized proton spectra were obtained using a Philips Gyroscan 1.5 T combined imaging and spectroscopy system (2). Multislice images were obtained in three planes.…”
Section: Methodsmentioning
confidence: 99%
“…Myo-inositol is a precursor of second messengers and a constituent of membrane lipids (Kofmann et al, 1991;Miller 1991;Ross, 1991). The highest peak of the proton spectrum usually results from NAA (Barany et al, 1987;Frahm et al, 1989;Luyten et al, 1991); NAA is found in high amounts in the brain, but not in other tissue (1/1000 of brain weight). It was observed in neurons and oligodendrocytes (Urenjak et al, 1992(Urenjak et al, , 1993.…”
Section: Magnetic Resonance Spectroscopy and Cerebral Metabolitesmentioning
confidence: 96%
“…"Single shot" volume selection for localized single volume 'H NMR spectroscopy was achieved with a stimulated echo RF pulse sequence (21,(35)(36)(37)(38), whereby two out of the three 90" RF pulses were spatially selective in two orthogonal directions. Volume selection in the third direction was achieved by refocusing the stimulated echo by a 180" RF pulse which was spatially selective in that direction.…”
Section: Volume Selectionmentioning
confidence: 99%